IMPACT OF ANCHOR BORROWERS’ PROGRAMME ON HOUSEHOLD DIETARY DIVERSITY OF SMALLHOLDER MAIZE FARMERS IN EKITI STATE, NIGERIA - Akoh, J.P.; Acheneje, P. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed the impact of the ABP on household dietary diversity among smallholder maize farmers in Ekiti State, Nigeria. A census and multi-stage random sampling procedure were employed to select the respondents for this study. Primary data were collected from 364 smallholder maize farmers (172 participants and 192 non-participants) across the State using digital questionnaires. Descriptive statistics, Household Dietary Diversity Score (HDDS), and Propensity Score Matching (PSM) technique were adopted to analyse the data collected. The result revealed that ABP participants were generally male (60.47%), married (89.5%), well-educated (98% with formal education), and had significantly better access to extension services (67.44%). HDDS results showed that 38.4% of the participants demonstrated significantly higher levels of dietary diversity compared to 33.3% of non-participants, 73.8% of participants consumed more energy-providing food, compared to 44.3% of non-participants, 66.3% of participants consumed protein-rich foods compared to 42.2% of non-participants, 98.3% of participants consumed vitamins and minerals (vegetables and fruits), while only 15.6% of non-participants consumed vitamins and minerals. However, the PSM analysis revealed a statistically significant negative impact of ABP participation on household dietary diversity. Specifically, the Kernel Matching algorithm indicated that ABP participants had, on average, a 3.90-unit lower HDDS than comparable non-participants (p<0.01). Hence, the study concludes that the ABP, as implemented, failed to improve household food security among participating smallholder maize farmers in Ekiti State. The need to overhaul of the ABP’s implementation process and monitoring, alongside integrating nutrition, food safety, and preservation training into the extension curriculum is highly recommended, to ensure production gains translate into meaningful and sustainable improvements in household dietary and nutritional security.